Unveiling the multifaceted realm of human papillomavirus: a comprehensive exploration of biology, interactions, and advances in cancer management - Wu, Meng; Huang, Hui; Tang, Ying; Ren, Xuze; Jiang, Xinrui; Tian, Man; Li, Wei (Frontiers in Immunology, 2024)
Human Papillomavirus (HPV), an extensive family of DNA viruses, manifests as a persistent global health challenge. Persistent HPV infection is now firmly established as a significant aetiological factor for a spectrum of malignancies. In this review, we examine the latest insights into HPV biology and its intricate relationship with the host. We delve into the complex dynamics of co-infections involving HPV alongside other viruses, such as HIV, EBV, and HSV, as well as the burgeoning role of the microbiome in cancer development. We also explore recent advancements in understanding the specific contributions of HPV in the development of various cancers, encompassing cancers of the anogenital region, head and neck, as well as breast, lung, and prostate. Moreover, we focus on the current preventive strategies, including vaccination and screening methods, and therapeutic interventions that range from traditional approaches like surgery and chemotherapy to emerging modalities such as targeted therapies and immunotherapies. Additionally, we provide a forward-looking view on the future directions of HPV research, highlighting potential areas of exploration to further our understanding and management of HPV and its associated cancers. Collectively, this review is positioned to deepen readers' understanding of HPV biology and its complex interplay with cancer biology. It presents innovative strategies for the prevention, management, and therapeutic intervention of HPV-associated malignancies.